Use of Medicinal Plants in Eastern Part of Pokhara, Nepal (ZOO-Journal, 2019)
From the beginning of civilization, man's relationship with the surrounding plant resources has always been very intimate. This study provides information to the general people to protect such medicinal plants. Kumal ethnic community mainly lives in Thulo-Kumal Gaun and scattered in different parts of Pokhara valley such as Dhungepatan, Bhandardik and Patneri. Altogether 20 medicinal plant species were identified.